AIAA Atmospheric Flight Mechanics Conference 2016
DOI: 10.2514/6.2016-1753
|View full text |Cite
|
Sign up to set email alerts
|

Ground Vibration Tests on a Flexible Flying Wing Aircraft - Invited

Abstract: This paper presents ground vibration test results for a small flexible flying wing aircraft. The aircraft is suspended from a spring and an input force is applied via an electrodynamic shaker. Accelerometer measurements are obtained at twenty points along the aircraft wings. This measured force and acceleration data is post-processed to identify modal frequencies and mode shapes using two different methods. The effect of small changes in the experimental procedure on the identified modal parameters is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The measured force and acceleration data obtained is further post processed to determine the modal frequencies and mode shapes using Quadrature Response Method and Curve-Fitting Frequency Domain Decomposition (CFDD) [32]. The performed sabotage attacks will change the laminate properties, including its stiffness (see Table 3).…”
Section: Identification Of Sabotaged Partsmentioning
confidence: 99%
“…The measured force and acceleration data obtained is further post processed to determine the modal frequencies and mode shapes using Quadrature Response Method and Curve-Fitting Frequency Domain Decomposition (CFDD) [32]. The performed sabotage attacks will change the laminate properties, including its stiffness (see Table 3).…”
Section: Identification Of Sabotaged Partsmentioning
confidence: 99%
“…GVTs were recently conducted for both aircraft by suspending them from a spring and applying to them an input force via an electrodynamic shaker. 23 In each case, accelerometer measurements were recorded at twenty points along the aircraft wings, and the measured force and acceleration data were post-processed using two different methods to identify natural frequencies and mode shapes. The obtained natural frequencies are reported in Table 2 below, as documented originally in Reference.…”
Section: Real Ground Vibration Test Datamentioning
confidence: 99%
“…In Section V, the performance of the resulting nonparametric probabilistic approach for performing model-form UQ in generalized eigencomputations is illustrated for a natural vibration analysis problem associated with the mAEWing1 flying wing for which ground vibration test data are available. 23 Finally, conclusions are offered in Section VI.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of this nonparametric probabilistic method for the UQ of model‐form uncertainties in nonlinear structural dynamics problems was demonstrated in the aforementioned work . The method was extended to model‐form uncertainties arising in generalized eigenvalue computations in the work of Farhat et al, where its performance for such applications was demonstrated through the vibration analysis of two different real‐world aircaft for which experimental data is available . In the work of Farhat et al, the computational aspects of this method were refined by hyperreducing the SPROM to accelerate its execution time.…”
Section: Introductionmentioning
confidence: 99%
“…4 The method was extended to model-form uncertainties arising in generalized eigenvalue computations in the work of Farhat et al, 5 where its performance for such applications was demonstrated through the vibration analysis of two different real-world aircaft for which experimental data is available. 8 In the work of Farhat et al, 9 the computational aspects of this method were refined by hyperreducing the SPROM to accelerate its execution time. The potential of the resulting enhanced approach for quantifying model-form uncertainties in eigenvalue computations, while accounting for modeling errors due to hyperreduction, was demonstrated through what-if vibration analysis scenarios.…”
Section: Introductionmentioning
confidence: 99%